2009
DOI: 10.2174/156802609787354324
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of 5a-Carbaglycopyranosylamime Glycosidase Inhibitors

Abstract: 5a-Carba-alpha-D-glucopyranosylamine, validamine, and analogous compounds valienamine and valiolamine, have proved to be important lead compounds for development of clinically useful medicines, including the very strong alpha-glucosidase inhibitor, voglibose, N-(1,3-dihydroxyprop-2-yl)valiolamine, now used widely as a clinically important antidiabetic agent. In this review, we describe recent advances in development of glycosidase inhibitors on the basis of the ground-state mimics of the postulated glycopyrano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Thus, α-glucosidase inhibitors may be used as attractive therapeutic agents to reduce the rate of glucose absorption and consequently suppress the levels of postprandial blood glucose and insulin. It is also reported that α-glucosidase inhibitors can alter glycosylation and reduce the total amount of some glycoproteins produced. , Therefore, inhibiting the action of α-glucosidase may lead to the discovery of new therapeutic agents for these diseases. During the past few decades, considerable efforts have been devoted to the creation of α-glucosidase inhibitors, , which can be classified into sugar-mimicking and non-sugar types according to their structural features. To date, sugar-mimicking α-glucosidase inhibitors have been extensively studied, and some of them, including acarbose (Bayer), miglitol (Bayer), and voglibose (Takeda), have been clinically used to inhibit small intestinal α-glucoside hydrolases, such as α-glucosidase, glucoamylase (EC 3.2.1.3), and sucrase (EC 3.2.1.48) . Though non-sugar α-glucosidase inhibitors are essential as therapeutic agents in terms of diversity, they have not yet been well developed relative to sugar-containing inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, α-glucosidase inhibitors may be used as attractive therapeutic agents to reduce the rate of glucose absorption and consequently suppress the levels of postprandial blood glucose and insulin. It is also reported that α-glucosidase inhibitors can alter glycosylation and reduce the total amount of some glycoproteins produced. , Therefore, inhibiting the action of α-glucosidase may lead to the discovery of new therapeutic agents for these diseases. During the past few decades, considerable efforts have been devoted to the creation of α-glucosidase inhibitors, , which can be classified into sugar-mimicking and non-sugar types according to their structural features. To date, sugar-mimicking α-glucosidase inhibitors have been extensively studied, and some of them, including acarbose (Bayer), miglitol (Bayer), and voglibose (Takeda), have been clinically used to inhibit small intestinal α-glucoside hydrolases, such as α-glucosidase, glucoamylase (EC 3.2.1.3), and sucrase (EC 3.2.1.48) . Though non-sugar α-glucosidase inhibitors are essential as therapeutic agents in terms of diversity, they have not yet been well developed relative to sugar-containing inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Under prolonged heating, however, partial hydrolysis of the phthaloyl derivative to the intermediate phthalamic acid was sometimes observed (27) . During the last years, considerable attention have been devoted to the creation of αglucosidase inhibitors, which can be classified into sugar mimicking and non-sugar types according to their structural features (28)(29)(30) .Sugar-mimicking α-glucosidase inhibitors have been extensively studied, including: Acarbose,miglitol and voglibosehave been clinically used to inhibit small intestinal αglucoside enzymes, such as α-glucosidase and glucoamylase (31) . The synthesized compounds (5a, 5f, 6a) IC50 values: 5.18, 4.6, 7.3 respectively accordingly these compounds have excellent alphaglucosidase inhibitory activity in comparison with standard compound acarbose (IC50= 817.38 ± 6.27 M), These results could be attributed to generation new binding site with a hydrophobic pocket in the active site of enzyme, the secondary amine in 5-flouro uracil ring bind by an ionic bond, aromatic rings by hydrophobic bonds while oxygen, nitrogen, chlorine and fluoride atoms bind through hydrogen bonds.…”
Section: Spectral Data and Chemistrymentioning
confidence: 99%
“…Simple aminocarbasugars such as valienamine (31), validamine (32), hydroxyvalidamine (33), and valiolamine (34) appeared to be active against several sugar hydrolases [302,303]. Valienamine, validamine, and hydroxyvalidamine were reported as microbial oligosaccharide -glucosidase inhibitors [304][305][306][307].…”
Section: Aminocarbasugars Aminocarbasugarsmentioning
confidence: 99%